GAME EDUKASI MOBILE "AKU SUKA SAYUR" BERBASIS AUGMENTED REALITY UNTUK ANAK USIA DINI - Vivianti, Vivianti; Ratnawati, Dwi (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2021)
This research aims to develop a mobile based educational game application "I like vegetable" for preschoolers. The research method used in developing educational games is the research and development (RD) method adapted from Borg Gall with several stages, namely needs analysis, identification of product specifications, product development, product validation, product revision and product testing. This study involved 8 research respondents with the object of research being the mobile educational game "Aku Suka Sayur" with the Augmented Reality feature. Data was collected using a questionnaire filled out by the guardian of the respondent. This study uses descriptive analysis data analysis techniques.The final product is a mobile educational game application with the title "I Like Vegetables". Augmented Reality technology in the form of live coloring is applied in this educational game to increase children's attractiveness. The calculation results show that the feasibility score of the Augmented Reality-based educational game application developed is 93.75%, including the very feasible category. Augmented Reality technology allows interaction between applications and the environment. In other words, children do not only focus on smartphones, but also do other activities and interact with the environment.